2018
DOI: 10.1039/c8gc01763h
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery approach for lignocellulosic biomass valorisation with an acidic ionic liquid

Abstract: An acidic ionic liquid offers an exciting window to directly produce hemicellulose pentoses and to valorise cellulose and lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…The same IL was also reported as able to hydrolyse and to convert hemicellulose fraction of wheat straw with no additional catalyst used [17]. The pre-treatment with this IL produced a liquor rich in hemicellulosic sugars, furans and organic acids, and a solid fraction constituted mainly of cellulose and lignin.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The same IL was also reported as able to hydrolyse and to convert hemicellulose fraction of wheat straw with no additional catalyst used [17]. The pre-treatment with this IL produced a liquor rich in hemicellulosic sugars, furans and organic acids, and a solid fraction constituted mainly of cellulose and lignin.…”
Section: Introductionmentioning
confidence: 78%
“…Alternative approach of the biomass processing with IL is the employment of ILs as both solvent and catalyst. In these processes, ILs hydrolyse mainly polysaccharide fraction without the presence of other catalyst [5,16,17]. Therefore, ILs with acidic character demonstrated ability to selectively hydrolyse hemicellulose [18,19], both cellulose and hemicellulose [20], or lignin [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that up to 85% of the lignin and up to 100% of the hemicellulose were solubilized into the IL solution, and the hemicellulose dissolved mainly in monomeric form, and pentoses were partially converted into furfural. Up to 77% of the glucose contained in the biomass could be released by enzymatic saccharification of the pulp ,…”
Section: Introductionmentioning
confidence: 99%